Investigation of demulsification efficiency in water-in-crude oil emulsions using dissipative particle dynamics1. Issue 77 (22nd August 2015) - Song, Xianyu; Shi, Peng; Duan, Ming; Fang, Shenwen; Ma, Yongzhang
<x xml:space="preserve">Abstract</x> Demulsification efficiency with alternating hydrophobic blocks of the polyether is investigated by dissipative particle dynamics.